PENGUKURAN RESISTIVITAS LAPISAN TANAH DI KELURAHAN TUAH KARYA MENGGUNAKAN KONFIGURASI SCHLUMBERGER - Hafiza Mudral; Usman Malik (Prodi Fisika FST UNJA, 2019)
Geoelectric is one of the geophysical exploration methods that uses the earth's electrical properties to study subsurface conditions, the geoelectric method has several rules, one of which is Schlumberger's rule. This study aims to determine the composition of the soil layer, so that it can be known that the cause of difficult surface water seeps into the ground based on resistivity values at the HSB Indah Residence. Schlumberger configuration research uses a 300 meter stretch. Resistivity of soil constituent lithology in the study area was generated by processing geoelectric data using one-dimensional progress software. The cross section of the rock structure consists of five layers, namely the first layer is a clay layer with a resistivity value of 13.49 Ωm, the second layer is silt layer with a resistance value of 42.88 Ωm, the third layer is a clay layer with a value of 1.87 Ωm, the fourth layer is a layer of sandstone with a resistivity value of 59.17 Ωm and the fifth layer is a layer of gravel sand with a resistivity value of 443.40 Ωm. This shows that the cause of surface water is always flooded around the housing area, the soil layer is dominated by clay and silt material with a depth of more than 25 meters.